HUBUNGAN EXSPLOSIVE POWER OTOT TUNGKAI DENGAN HASIL LARI JARAK PENDEK (SPRINT) 100 METER SISWA YANG MENGIKUTI EKSTRAKURIKULER ATLETIK SMA NEGERI 15 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the correlation between the explosive power of leg muscles with the results of a 100 meter sprint short run of Athletic students in SMA Negeri 15 Pekanbaru. This research uses correlation research design. The sample in this study were students who participated in an athletic extracurricular 100 meter running number at SMA Negeri 15 Pekanbaru totaling 8 students. Based on the results of research and data processing using statistical research procedures, it was concluded that for the correlation of variable X to variable Y obtained r count = 0.956 and r table = 0.754 which means r count (0.956)> r table (0.754). This shows that there is a correlation between Leg Muscle Explosive Power and the results of Short Distance Running (Sprint). With this result Ha was accepted and Ho was rejected.Key Words: Correlation of Exsplosive Power of Leg Muscles, Sprint Running